How to Increase Students' Interest in Learning Throught TGT Type Cooperative Learning at SDN Keleyan 2 - Dwiyanti, Aprilia; Oktavia, Elda; Aisyi, Faradiba Rohadatul; Setyawan, Agung; Alwi, Syarifah Rafidah Wan (Sekolah Tinggi Agama Islam Nurul Islam Mojokerto, 2024)
Team Games Tournament (TGT) type cooperative learning model was used in this research to increase students' interest in learning in science subjects regarding human and animal organs. This research is Classroom Action Research which consists of the stages of Planning, Implementation, Observation and Follow-up. Conducted in class V at SDN Keleyan 2 for two cycles. In cycle I, achievement was still low, so improvements were made in cycle II. The results of cycle II show that the use of the TGT learning model succeeded in increasing students' interest in learning.